THE NEW DIMENSION OF THREATS THAT THE EUROPEAN ACTORS ARE SUBJECT TO IN NEIGHBORING STATES CRISIS MANAGEMENT - DĂNILĂ VALENTIN-BOGDAN; DĂNILĂ MARIAN-ALIN (Challenges of the Knowledge Society)
Restructuring activities of the current international system increases the amplification of the existing inequalities in developing countries with unlimited potential for the European market. Thus, amid security system vulnerabilities and uncontrolled situations, the local conflicts may spread to neighboring regions, affecting also the strategic security environment. The dynamics of political and military events reveals that security and defense go beyond the responsibility of a single country, a fact which causes a greater involvement of democratic states and international organizations. Against this background, the work in question provides not only an insight into the new international dimension, but also a possible response version in order to enable risk and vulnerabilities (of economic, social or religious nature) management, in the benefit of all. Therefore, restricting undesirable phenomena can be achieved by harmonizing the actions on the various interest sectors at national or international level, similar to the objectives underlying the American concept of "homeland security". As a solution, the concept itself connects everything that can be connected, when we talk about security, in a widespread network of state intervention mechanisms, namely, the external instruments of power. For this reason, homeland security is characterized by a plurality of stakeholders, from a local and national level to a European and transatlantic one.